(untitled) (Journal of Science and Technology, 2016)
Buruli ulcer, a tropical, swampy climate disease, is one of the commonest diseases associated with most typical villages such as those in the Bomfa sub-district of Ejisu-Juaben District in the Ashanti Region of Ghana. In response to the World Health Organization’s guidelines on the use of Buruli ulcer chemotherapy a study was conducted to investigate the role of surgery combined with chemotherapy in the control of Buruli ulcer in this endemic area. In all 62 patients within the period January 1st till December 31st 2005 ranging from 4 to 79 years were treated through the combination of surgery and chemotherapy, 72.6% of which had their lesions on their lower limbs. The sizes of edematous forms reduced by 80% as a result of chemotherapy thereby enabling lesser area of excision as compared to the pre-chemotherapeutic era. There was a 50% reduction in the number of multiple surgeries per patient as compared to the pre-chemotherapeutic era. The “dual” mode of treatment (chemotherapy + surgery) reduced hospitalization period to 44.2% which should directly reduce the cost of treatment. Follow-up on these patients recorded no signs of recurrence. The recommended dosage of Rifampicin and Streptomycin - the Buruli chemotherapeutic drugs - was strictly adhered to in the treatment protocol.